Protective Effects of Regular Exercise Combined With Curcumin Supplementation Against Lead-Induced Cerebellar Oxidative Damage in an Animal Model - Habibian, M.; Moosavi, J.; Farzanegi, P. (Нейрофизиология, 2016)
Lifestyle modifications, such as physical exercise and dietary supplements, were recommended
as protective measures against some neurological disorders. We examined the effects of
regular exercise combined with curcumin supplementation against lead-induced oxidative
damage of the cerebellum in male rats. Experimental animals (n = 50) were randomly divided
into five groups. Lead acetate (20 mg/kg) was i.p. administered to three groups (except sham
and control ones), while the sham group received ethyloleate (30 mg/kg) three times per
week. The curcumin and curcumin + exercise groups received curcumin (30 mg/kg) i.p. five
times per week for eight weeks. The exercise program consisted of progressive running on
a treadmill, speed from 15 to 22 m/min, 25 to 64 min per day, five times per week for eight
weeks. Two days after the last application, the rats were euthanized, and their cerebellum
was removed and homogenized to measure the levels of brain-derived neurotrophic factor
(BDNF) and thiobarbituric acid-reactive substances (TBARSs). Chronic administration
of lead significantly increased the cerebellar TBARS levels but did not alter considerably
the BDNF levels. Curcumin and curcumin + exercise treatments significantly lowered the
cerebellar TBARS levels; a significant increase in the BDNF level was observed in the
cerebellum of rats treated with combined intervention. Thus, regular exercise combined with
curcumin supplementation may exert a significant neuroprotective effect against lead-induced
cerebellar injury by attenuating oxidative stress and improving the brain state through an
increase in the BDNF amount. Модифікації стилю життя, такі як фізичні тренування та
вживання добавок до дієти, рекомендуються як протективні
заходи щодо низки неврологічних розладів. Ми дослідили
впливи регулярних тренувань, поєднаних з уведенням куркуміну, на індуковане свинцевою інтоксикацією оксидативне ушкодження мозочка у самців щурів. Експериментальні
тварини (n = 50) були рандомізовано поділені на п’ять груп.
Ацетат свинцю (20 мг/кг) уводився тваринам трьох груп (дві
слугували контролем). Одна з контрольних груп отримувала етилолеат (30 мг/кг) тричі на тиждень. У двох інтоксикованих групах тварини отримували 30 мг/кг куркуміну п’ять
разів на тиждень протягом восьми тижнів. Програма тренувань включала в себе прогресивно збільшувані епізоди бігу
на тредбані (від 15 до 25 м/хв, від 25 до 64 хв/добу, п’ять разів на тиждень протягом восьми тижнів). Через дві доби після закінчення курсів щурів піддавали евтаназії, мозочок видаляли та гомогенізували для вимірювання рівнів мозкового
нейротрофічного фактора (BDNF) та речовин, реактивних
щодо тіобарбітурової кислоти (TBARSs). Хронічне введення свинцю викликало вірогідне збільшення рівнів TBARS,
але не змінювало істотно рівнів BDNF. У групах «куркумін»
та «куркумін+тренування» спостерігалися значно нижчі рівні TBARS; вірогідно більший рівень BDNF у мозочку відмічався в групі з комбінацією заходів. Отже, регулярні фізичні тренування, поєднані з уведенням куркуміну, можуть
забезпечити істотний протекторний ефект щодо індукованого свинцем ушкодження мозочка, опосередкований зменшенням оксидативного стресу та поліпшенням стану мозку
завдяки певному збільшенню кількості BDNF.